Oleophilicity and oil-water separation by reduced graphene oxide grafted oil palm empty fruit bunch fibres - Mohd Shaiful Sajab; Wan Nurmawaddah Wan Abdul Rahman Jauhari; Chia, Chin Hua; Sarani Zakaria; Hatika Kaco; An'amt Mohamed Noor (Penerbit Universiti Kebangsaan Malaysia, 2018)
Absorption is one of the effective, simple and economical methods to remove oil from oily wastewater. The most widely used approach is to utilize lignocellulosic biomass as oil absorbent. However, the hygroscopic of cellulose have limited the oil-water separation capability of lignocellulosic fibers. In this study, the surface functionality of oil palm empty fruit bunch (EFB) fibers was slightly altered by grafting reduced graphene oxide (rGO). The modified EFB fibers show a distinct morphological and chemical characteristics changes as the surface of fibers has been coated with rGO. This was supported by FTIR analysis with the diminishing peak of hydroxyl group region of EFB fibers. While the surface modification on EFB fibers shows a diminution of a hydrophilic characteristic of 131.6% water absorption in comparison with 268.9% of untreated EFB fibers. Moreover, modified fibers demonstrated an oil-water separation increment as well, as it shows 89% of oil uptake and improved ~17 times of oil selectivity in oil-water emulsion than untreated EFB fibers.